Silence of TGF-β1 gene expression reduces prrsv replication and potentiates immunity of immune cells of tibetan pig. (December 2019) - Wang, Ye; Chen, Yihui; Liang, Ge; Zeng, Kai; Chen, Xiao-hui; Ying, San-cheng; Wang, Zezhou; Lv, Xue-Bin; Gao, Rong
Highlights: Knockdown of TGF-β1 gene expression by shRNA inhibited PRRSV replication in pig immune cells and increased the viability of infected cells. Silencing TGF-β1 gene expression by shRNA enhanced the antiviral immunity and reduced PRRSV yield in the infected cells. Silence of TGF-β1 gene expression by shRNA can facilitate the control of PRRSV infection in pigs. Abstract: Transforming growth factor beta 1 (TGF-β1) was of importance in the pathogenesis of porcine reproductive and respiratory syndrome virus (PRRSV). To determine whether knockdown of TGF-β1 gene expression could facilitate the control of PRRSV infection, specific sequences for expressing shRNA targeted to porcine TGF-β1 gene were synthesized and cloned into pSilencer 3.1-H1 neovector. Then they were used to transfect peripheral blood mononuclear cells of Tibetan pig (Tp-PBMCs) followed by PRRSV inoculation. The positive recombinant plasmids were screened for inhibition of TGF-β1 gene expression by real-time quantitative RT-PCR. Conversely, the mRNA level of PRRSV in shRNA treated Tp-PBMCs dramatically decreased, and there were significant increases of the transcription of immune genes, such as interleukin-2 (IL-2), interleukin-4 (IL-4), interferon-alpha (IFN-α), interferon-gamma (IFN-γ), tumor necrosis factor-alpha (TNF-α), toll-like receptor 3 (TLR3), toll-like receptor 7 (TLR7), Myeloid differentiation primary response gene (88) (MyD88), and interleukin-27p28 (IL-27p28). However, the expressions of IL-8 and IL-10 genes significantly reduced in comparison to the control infected cells. In addition, transfection with the shRNA plasmids significantly elevated the viability of immune cells. Therefore the knockdown of TGF-β1 gene expression by shRNA not only inhibits the replication of PRRSV but also improves immune responsiveness following viral infection, suggesting a novel way to facilitate the control of PRRSV infection in pigs.